Schema reliance and innocent alibi generation - Leins, Drew A. (Legal and criminological psychology, 2016)
Purpose. Alibis are critical components of innocent suspects' efforts to prove their innocence. However, they can often be inaccurate. Two experiments explored factors influencing innocent alibi generation. Experiment 1 tested the effect of retrieval cue (time vs. location vs. paired time and location) on report accuracy and schema reliance. Experiment 2 tested the effect of the schema consistency of critical whereabouts (consistent vs. inconsistent) on alibi accuracy and schema reliance. Methods. Both experiments used the same paradigm: Participants engaged in a critical event (two events in Experiment 2), then participated in an ostensibly unrelated study occurring roughly 1 week later. During this unrelated study (in reality, the alibi generating portion of this study), participants were interviewed about their whereabouts for various times during the previous week (including the times of the critical events). Alibis were scored for accuracy and schema consistency. Results. In Experiment 1, a time cue and a paired time and location cue yielded lower rates of accuracy than did a location cue. Cues including a time referent yielded high rates of schema reliance. In Experiment 2, accuracy was lower when whereabouts were schema inconsistent than when they were schema consistent. Confidence was high across conditions, irrespective of accuracy. Conclusion. Time cuing appears to elicit schema reliance when generating alibis. Schema retrieval may inflate confidence in accuracy; thus, schema reliance may lead to inaccurate reporting, particularly when critical whereabouts are atypical.